Remittances and firm performance in sub-Saharan Africa : evidence from firm-level data - (:unkn) unknown (My University, 2021)
Sub-Saharan African firms face enormous obstacles to their development. The main constraints to business performance identified are poor access to finance and a weak domestic market. In this paper, we examine how international remittances affect firms' performance. Specifically, we investigate the role of remittances on capital accumulation, sales, and employment in 34,010 firms operating in 42 Sub-Saharan African countries between 2006 and 2020. Using a fixed-effect instrumental variable approach to control for the endogeneity of remittances, we find that international remittances positively affect the share of capital held by nationals in manufacturing firms. Moreover, international remittances positively affect sales in non-manufacturing firms, while a negative effect on the sales of manufacturing firms is observed. Regarding the effect of remittances on employment, we find a positive impact on both manufacturing and non-manufacturing firms. Heterogeneity tests suggest that the effect of remittances on firms' performance is larger in less financially developed and non-resource-rich countries. As for the negative impact of remittances on sales in manufacturing firms, the results show that it is entirely due to small firms. Finally, using remittances per capita instead of remittances relative to GDP, similar result are found.
Keywords: African Research